Structure formation during continuous cooling of deformed austenite of boron-containing steel - Sobolenko , M.A.; Romanova , N.S. (Theory and Practice of Metallurgy, 2025)
Purpose. To establish the regularities of the formation of the structure of 30G1R steel during cooling at different rates from the heating temperature of 1030 -1040 ℃. To analyze the kinetics of the decomposition of deformed austenite of low-carbon boron-containing steel. Methodology. Studies of structural-phase transformations and the kinetics of the decomposition of deformed austenite were carried out using the method of differential thermal analysis on samples of boron-containing steel with studies of microstructure and hardness. Findings. The kinetics of transformations of structural components was studied and a thermokinetic diagram of the decomposition of deformed austenite of boron-containing steel was constructed, taking into account the influence of hot plastic deformation. The peculiarities of the influence of the cooling rate of deformed austenite on the volume fraction of structural components of the studied steel were revealed. Originality. The influence of temperature-deformation conditions and cooling regimes after deformation on the features of the structure formation of boron-containing steel is shown. The influence of the cooling rate on the nature of the transformations of deformed austenite and the mechanical properties of the studied steel is revealed. Practical value. The conducted studies of the decomposition of hot-deformed austenite of 30G1R steel allow us to reasonably approach the development of modes and production technology for cold-rolling with the formation of optimal properties in the hot-rolled state. Cooling rate intervals have been established that ensure the formation of the required structure, consisting mainly of highly dispersed quasi-eutectoid and self-tempered bainite, which is the basis for the implementation of progressive types of spheroidizing treatments of steel.